2007
DOI: 10.1039/b617388h
|View full text |Cite
|
Sign up to set email alerts
|

An iron-catalysed hydrosilylation of ketones

Abstract: The combination of Fe(OAc)2 and multi-nitrogen-based ligands such as N,N,N',N'-tetramethyethylenediamine, bis-tert-butyl-bipyridine, or bis(oxazolinyl)pyridine can efficiently catalyse hydrosilylation of ketones to give the corresponding alcohols in high yields including asymmetric catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(83 citation statements)
references
References 38 publications
1
79
1
2
Order By: Relevance
“…Electrondeficient as well as electron-donating groups on the aryl ring did not show any significant influence on the activity of the iron catalyst. Interestingly, functional groups such as CN, Br remained unchanged under such reaction conditions ( Table 2, entries [8][9][10].…”
Section: Entries 18 and 19)mentioning
confidence: 94%
See 2 more Smart Citations
“…Electrondeficient as well as electron-donating groups on the aryl ring did not show any significant influence on the activity of the iron catalyst. Interestingly, functional groups such as CN, Br remained unchanged under such reaction conditions ( Table 2, entries [8][9][10].…”
Section: Entries 18 and 19)mentioning
confidence: 94%
“…In contrast to aldehydes, aryl methyl ketones bearing substituents in the ortho-position of the aryl ring led to the corresponding alcohols in 68-99% isolated yield, which shows that ortho hindered substituents can hamper the reaction (Table 3, entries 2/3 and 4/6). The hydrosilylation reaction was suitable to both electron-rich and electron-poor substituted (Me, OMe N-morpholinyl, Br) aromatic methyl ketones, and the reaction gave the corresponding alcohols in good to excellent yields (68-99%; Table 3, entries [1][2][3][4][5][6][7][8]. The principle of this iron-catalyzed transformation can also be extended to heterocyclic methyl ketones such as 2-pyridyl methyl ketone (Table 3, entry 11), to a-tetralone (Table 3, entry 12) or to benzophenone derivatives such as 4,4'-dimethylbenzophenone (Table 3, entry 13).…”
Section: Entries 18 and 19)mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Recently,e nvironmentally benign and less expensive catalysts have also been exhaustively exploredl eading to broad acceptance of earth-abundant metals such as zinc [3] and iron [4] in asymmetric synthesis. Particularly stimulating progress has been observed recently in the asymmetric hydrosilylation of ketones promoted by ironc omplexes.S ince Nishiyama [5] and Beller [6] reported the first examples of Fe(OAc) 2 -catalyzed asymmetric hydrosilylation with (EtO) 2 MeSiH and (EtO) 3 SiH, manyi ron-based catalysts have been studied for the asymmetric hydrosilylation of ketones.[7] However, ironc omplexes are often sensitive to the reactionc onditions due to the easy oxidation of iron(II)a nd also require relatively elevatedt emperatures. Only recently, an example of am ore reactive and enantioselective iron complex with the boxmi ligand has been presented by Gade.…”
mentioning
confidence: 99%
“…7 Nishiyama et al have shown that TMEDA acts as a powerful ligand for the hydrosilylation of ketones. 8 TMEDA also promotes regioselective ring opening of aziridines with trimethylsilylated nucleophiles. 9 Sano et al 10 demonstrated that TMEDA could induce the acylation of alcohol with benzoyl chloride.…”
Section: Introductionmentioning
confidence: 99%